El Acuerdo de Gobierno a Gobierno y los Contratos NEC: ¿Soluciones a las deficiencias de la normativa de contrataciones del Estado que puedan ser replicadas por todas las entidades? - Medina Flores, Juan Carlos (2019)
Within the main contracting mechanisms used by the Special Project in charge of the organization and development of the X VIII Pan American Games and VI Parapan American Games of 2019 for the acquisition of complex and sophisticated goods, services and infrastructure, considering the lack of national experience in mega sport events, we can find Government-to-Government Agreements and New Engineering Contracts.Considering the results of these contracting mechanisms, there are many public entities evaluating the possibility to use them to carry out their own projects. However, it is not unusual for these entities to not fully understand the scope and nature of said mechanisms.Therefore, this paper explains the main characteristics of these two contractual figures, as well as the experience of their use in the Pan American Games, in order to appoint some considerations that public entities must take into account before deciding to use them.